De fureur et de sang - Léa Jaurégui; Jeanne Mathas (Les Cahiers de l'École du Louvre)
A focus on the practical use of blood and its metaphorical evocation offers the opportunity for a reinterpretation of the mutations, plurality and rivalry on the Western art scene of the 1970s through the prism of the questioning of gender and denunciations of latent and invisible discrimination. Focusing on a number of emblematic works by female artists, the analysis endeavours to elucidate the entanglement of feminist struggles in and on the margins of aesthetic tendencies formed – through shared militant commitment – of common values but above all their intractable plastic variety.